STRATEGI GURU EKONOMI MENGGUNAKAN MEDIA PEMBELAJARAN ALTERNATIF PADA SEKOLAH DENGAN PEMBATASAN GAWAI - Auliya Anjani, Ayu; Ekbal Santoso; Muhammad Anasrulloh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The policy of restricting student device use at MA Darul Hikmah Tulungagung encourages economics teachers to develop alternative, non-digital learning media to ensure effective learning. This study aims to analyze economics teachers' strategies in using alternative learning media, including media types and characteristics, design and implementation processes, student responses and involvement, and obstacles and solutions. The study employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that teachers used visual media in the form of images and